2002
DOI: 10.1080/00038628.2002.9696948
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Design and Scientific Aspects for Drencher Systems in Different Countries

Abstract: For spaces without compartmentation, or where it is not possible to provide compartmentation, drencher system might be installed to preuent heat transferfiom the fire zone to the adjacent areas. Spaces with large openingssuch as refugefifloor also have this requirement. But questions had been raised on whether thedrenchersystem iseffective in providingft'resafety, especially when used aternally under wind environment, In thispaper, designguides on thissystem in diffment countries including UK, USA and Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…As reported earlier on the retail shops by Ng and Chow (2002) about 70 to 80% of transmitted radiant heat intensity from the fire zone to the protected zone can be reduced by a water curtain. To avoid the huge amount of radiant heat being transmitted, double water curtain might be considered.…”
Section: Compartmentationsupporting
confidence: 54%
“…As reported earlier on the retail shops by Ng and Chow (2002) about 70 to 80% of transmitted radiant heat intensity from the fire zone to the protected zone can be reduced by a water curtain. To avoid the huge amount of radiant heat being transmitted, double water curtain might be considered.…”
Section: Compartmentationsupporting
confidence: 54%
“…Rahkonen [11,12] proposed that the heat stress caused by temperature difference on the glass surface was the main reason for glass fracture. The heat can be isolated by covering the glass surface with a water film via a sprinkler system, which protects the glass from being damaged [13][14][15]. Wu et al [16,17] verified through experiments that a water film could prevent glass from breaking in the event of fire.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson and Chown 16 found that the minimum sprinkler water flow rates to prevent dry spots from forming on the glass appear to be 70-90 L min 21 m 21 width, but lower flow rates may provide sufficient protection. 17 Ng and Chow 18 summarized the design and scientific aspects for drencher systems in different countries.…”
Section: Introductionmentioning
confidence: 99%